Influence of Brand Images and Prices on Consumer Purchase Decisions at PT. Unza Vitalis In Makassar - Haris, Abdul (Patria Artha Management Journal, 2018)
The purpose of this study are: 1) to determine and analyze the influence of brand imageon consumer purchasing decisions at PT. UnzaVitalis in Makassar, 2) to find out andanalyze the influence of prices on consumer purchasing decisions at PT. Unza Vitalis inMakassar.The analytical method used in this study is a multiple regression analysis method.Research data obtained from product customers of PT. Unza Vitalis in Makassar. Theresearch approach is an explanatory causal approach.The results showed that 1)variable brand image had a positive and significant effect on consumer purchasingdecisions at PT. Unza Vitalis in Makassar. This means that the better the company'sbrand image, the consumer purchasing decisions will increase, and 2) price variableshave a positive and significant effect on consumer purchasing decisions at PT. UnzaVitalis in Makassar. This means that according to the price offered by the company,consumer purchasing decisions are increasing.